Tautomerization of 5-Alkylidene-2-Oxazolidinone to 2-Oxazolone by Use of an N-Heterocyclic Carbene Catalyst - Fujita, Ken-ichi; Sato, Junichi; Yasuda, Hiroyuki (Synlett, 2015)
By employing an N-heterocyclic carbene as a catalyst, the tautomerization of 5-alkylidene-2-oxazolidinone proceeded to afford the corresponding 2-oxazolone. Among N-heterocyclic carbenes, 1,3-di-tert-butylimidazol-2-ylidene was the most effective catalyst for the tautomerization of 5-alkylidene-2-oxazolidinone.
Keywords: carbenes; catalysis; 5-alkylidene-2-oxazolidinone; tautomerization; 2-oxazolone